2018
DOI: 10.1186/s13075-018-1775-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative videocapillaroscopy correlates with functional respiratory parameters: a clue for vasculopathy as a pathogenic mechanism for lung injury in systemic sclerosis

Abstract: BackgroundTo determine whether lung involvement is related to microvascular perturbations, nailfold videocapillaroscopy (NVC) was performed in patients with systemic sclerosis (SSc).MethodsA cross-sectional study was consecutively accomplished in 152 SSc patients. NVC, a pulmonary function test and echocardiography were undergone within a 3-month period. Finally, 134 patients with at least eight NVC (200× magnification) images were selected for quantitative and qualitative examinations.ResultsPatients with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…active and late scleroderma pattern, or a conversion over time to worse scleroderma patterns, are associated with (incident) right heart catheterization defined SSc-PAH. Of note, post hoc, after the completion of this systematic review, a cross-sectional study by Guillén-Del-Castillo et al was published, reporting a negative correlation of higher capillary density and a positive correlation of number of abnormal shapes ("neoangiogenesis") with right ventricular systolic pressure in SSc-PAH patients compared to SSc-noPAH patients (38).…”
Section: Discussionmentioning
confidence: 93%
“…active and late scleroderma pattern, or a conversion over time to worse scleroderma patterns, are associated with (incident) right heart catheterization defined SSc-PAH. Of note, post hoc, after the completion of this systematic review, a cross-sectional study by Guillén-Del-Castillo et al was published, reporting a negative correlation of higher capillary density and a positive correlation of number of abnormal shapes ("neoangiogenesis") with right ventricular systolic pressure in SSc-PAH patients compared to SSc-noPAH patients (38).…”
Section: Discussionmentioning
confidence: 93%
“…Mean FVC was 73,83 (15,9)%, the regression rate for patients with ILD was 7,6 (6,73)%; mean DLCO was 60,82 (20,35)% and the mean regression rate for patients with ILD was 8(9,15)%. Mean sPAP was 32,49 (15,79)mmHg with a mean progression of 12,57 (15,11) mmHg.…”
Section: Resultsmentioning
confidence: 95%
“…Prior publications have found correlations between baseline specific quantitative NVC studies and lung function test or sPAP. The group of Guillén-Del-Castillo identified that the number of capillaries with neoangiogenesis, male gender and the presence of ILD on HRCT were factors independently associated with lower FVC values (15). SSc patients with ILD had a lower capillary density and a higher number of capillaries with neoangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Abs: autoantibodies, ILD: interstitial lung diseases, FTLs: fingertip lesions, NVC+: nailfold videocapillaroscopy positivity, PAH: pulmonary artery hypertension, RP: Raynaud's phenomenon, Skin: skin involvement and T: telangiectasia. According to SSc classification criteria [27], patients can be classified with a minimum of 9 points. FTL can be weighted with 2 or 3 points based on the presence of distal tip ulcers or pitting scars.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, none of these factors have been proven to influence significantly NVC [23][24][25]. Conflicting results are also reported regarding the association between PFTs and NVC in SSc, no association was reported in IPF and evidences in other ILDs are totally lacking [26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%